Let's not talk about sex. Issue 11 (17th October 2017) - Love, Melanie; Farber, Barry A.
Abstract: This article uses both a case illustration and data from a large‐scale survey of outpatient clients (N = 798) to understand the client's perspective about avoiding or being dishonest with his or her therapist about sexual topics. The case study, of a gay young man working with a heterosexual female therapist, explores this client's experience of what happens when it feels impossible to be forthcoming about sex and sexuality. Based on the findings of our study, we note clients' motives for avoiding these intimate yet important areas (e.g., shame), their perception of how this impacts the therapy process (e.g., impedes clinical progress), and their sense of therapist responses and attitudes that could increase their ability to be more honest ("just ask"). We discuss ways in which therapists can facilitate a more open dialogue about sexual material while attending to clients' concerns about doing so.